KUALITAS SEMEN SAPI PEJANTAN SIMMENTAL DAN LIMOUSIN YANG DIPELIHARA DALAM TIPE KANDANG YANG BERBEDA DI BALAI INSEMINASI BUATAN LEMBANG - Lagu, Bastiana Elvira; Pudjihastuti, Endang; Paputungan, Umar; Adiani, Sri (Universitas Sam Ratulangi, 2020)
SEMEN QUALITY OF LIMOUSIN AND SIMMENTAL BULLS MAINTAINED IN DIFFERENT TYPES OF PENS AT THE INSTITUTION OF LEMBANG ARTIFICIAL. The intensive maintenance of bulls included animal house and pens protecting animals against sunlight, cool effect, rain, high speed of win and other predators. Objective of this study was to evaluate effects of single bull in a pen (SB) and double bulls in a pen (DB) on semen quality of Limousin and Simmental bulls at the Institution of Lembang Artificial Insemination in West Java. Primer and secondary data of both bulls reproduction were used in this study and analyzed by t test method. Results showed that average volume of semen in both bulls of Limousin and Simmental under SB (9.54 ± 2.19 mL/ejaculation) was significantly higher of 7.67 percents than those of bulls under DB (8.86 ± 1.79 mL/ejaculation). The average of percentage of spermatozoa motility in both bulls of Limousin and Simmental under DB (71.00 ± 2.67) was not significantly differ with those of bulls under SB (70.10 ± 2.37). The average of spermatozoa mass movement in both bulls of Limousin and Simmental under SB (1.84 ± 0.37) was significantly more aggressive of 5.43 percents than those of bulls under DB (1.94 ± 0.24). Finally, the average of pH of semen in both bulls of Limousin and Simmental under SB (6.66 ± 0.11) was not significantly differ with those of bulls under DB (6.64 ± 0.10). Correlation between reproduction variables of both Limousinand Simmental bulls in SB and DB was not correlated between one and another variables indicated by correlation values ranging from -0.29 to 0.18. Based of the result of study can be concluded that semen quality of Limousin and Simental in single pen was better than that in double pens. The correlations among reproductive veriables of Limousin and Simmental in both sigle and double pens had no correlation between one and another variable. Keyword: Type of Pen, Semen Quality, Simmental Bull, Limousin Bull.